Hubungan Antara Minat Belajar dan Perhatian Orang Tua Terhadap Prestasi Belajar Geografi Kelas X SMA Negeri 2 Buru Selatan - Siti Lesilawang; Ferdinand Salomo Leuwol; Mohammad Amin Lasaiba (Jurnal Pendidikan Geografi Unpatti, 2025)
This study aims to analyze the relationship between learning interest, parental attention, and the academic achievement of tenth-grade students at SMA Negeri 2 Buru Selatan in Geography. The research employed a quantitative approach with a correlational design. Data were collected through questionnaires measuring learning interest and parental attention, as well as academic records. Data analysis was conducted using simple linear regression and multiple linear regression techniques to examine the relationships between variables. The results showed that the average student learning interest score was 60.5, with most students classified as moderate to good. Parental attention also had a positive impact on students' academic achievement, particularly in terms of academic supervision and motivation. The majority of students achieved good (B) and excellent (A) academic performance, with the highest score being 95 and the lowest 81. This study concludes that students' learning interest and parental attention significantly contribute to their academic success. Therefore, collaboration between students, parents, and schools is essential in fostering a more supportive learning environment.